O-011 Long term outcome in the repair of spinal cord perimedullary arteriovenous fistulae. (16th November 2010) - Hetts, S; Antonietti, L; Sheth, S; English, J; Dowd, C; Higashida, R; Lawton, M; Halbach, V
Abstract : Background and purpose: The natural history of perimedullary arteriovenous fistulae (PMAVFs), also known as type IV spinal cord AV fistulae, is incompletely understood. Both open surgical and endovascular approaches have been described as treatment modalities for this disease. The goal of this study was to evaluate the long term outcome of patients with PMAVFs treated at a single tertiary care institution. Materials and methods: We conducted a retrospective study on 32 patients with PMAVFs, evaluated between 1983 and 2009. Data were gathered by reviewing outpatient clinic notes, operative and radiological reports, and spinal angiograms. The PMAVFs were categorized into one of three types based on the angiographic imaging criteria. Pretreatment and post-treatment ambulation and micturition symptoms were quantified using the Aminoff and Logue scale (ALS). Results: 30 patients underwent corrective procedures, four by embolization alone, 11 by surgery alone and 15 patients received a combination of the two. 28 patients underwent follow-up spinal angiography, with residual shunting noted in six patients. Mean follow-up period was 54 months (range 1–228). Analysis of the ALS scores revealed that treatment of PMAVFs, independent of modality, resulted in significant improvement in ambulation, but inconsistent changes in micturition. In addition, residual fistula at the time of follow-up angiogram was associated with worsened neurologic status or lack of improvement. Outcome analysis based on fistula type showed dramatic improvement in ALS ambulation scores (62%) for type 3 fistulae compared with type 1 and 2 (26%, 27%, respectively). Conclusion: Significant improvement in ambulation, but not micturition, was observed following treatment. Residual fistula on follow-up angiography was associated with progressive worsening or lack of improvement in neurologic function. Patients with type 3 fistulae were shown to benefit most from treatment, with marked improvement in post-treatment ambulation scores. As endovascular and surgical techniques continue to evolve, further studies are warranted.